Menuju Keberlanjutan Lingkungan: Keterlibatan Masyarakat dalam Pengelolaan Sampah Kota Batam - Eva Lesna Nainggolan; Karol Teovani Lodan; Lubna Salsabila (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
Community engagement is crucial for successful development initiatives and rural community empowerment. This study focuses on analyzing community participation in an empowerment program in Batam City. The challenge lies in disseminating information about local regulation No. 11 of 2013 to a growing population. Current information dissemination methods, including print and electronic media, have limitations in reaching newcomers effectively. Despite consistent socialization efforts by the Batam City Environment Service, public awareness of environmental cleanliness remains insufficient due to a lack of attachment to the surroundings. To address waste management effectively, Regional Regulation Law No. 11 of 2013 plays a vital role. Ongoing socialization programs by the Batam City Environment Service are essential for program effectiveness. The study emphasizes the importance of community engagement and the need for tailored strategies to foster environmental stewardship in Batam City.